Susceptibility of Rhyzopertha dominica (Coleoptera: Bostrichidae) and Sitophilus oryzae (Coleoptera: Curculionidae) to the fungal entomopathogen Beauveria bassiana (Balsamo-Crivelli) Vuillemin s.l. (Hypocreales: Clavicipitaceae) - Vianna, Florencia; Russo, Leticia; Troncozo, Ines; Ferreri, Natalia; de Abajo, Juan Manuel; Scorsetti, Ana Clara; Pelizza, Sebastian (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
Control measures of stored grain pests include the excessive utilization of chemical insecticides that generate negative environmental impact. Current trends in integrated pest management are oriented towards the preservation of the environment using natural biopesticides, among these products arise entomopathogenic fungi. This study aimed to test the efficacy of a native strain of Beauveria bassiana to control two main stored grain pests such as Sitophilus oryzae and Rhyzopertha dominica and also evaluate the persistence of the fungus on wheat grains. The B. bassiana strain controlled 89%±0.07 of R. dominica adults and 80% ±0.14 of S. oryzae. The survival analysis showed that MST was 4.27 ±0.19 days for R. dominica adults and 4.27 ±0.20 days for S. oryzae. Furthermore, results of long rank test for the comparison of the Kaplan-Meier curves did not present significant differences between the survival of both stored grain pests. Dual choice tests demonstrated that B. bassiana LPSc1227 presented a repellent action against both stored grain pests. The seed persistence of conidia was 100% in treated seeds after 45 days. Further research will contribute to elucidate more insecticidal features of the B. bassiana LPSc 1227 strain against S. oryzae and R. dominica, two main stored grain insect pests. Highlights: bassiana presented insecticidal activity against R. dominica and S. oryzae. bassiana demonstrated a repellent action against both stored grain pests. bassiana was able to persist on the surface of wheat grains after 45 days storage.